Uniportal VATS Approach in Esophageal Cancer – How to Do It Update - Batirel, Hasan (Frontiers in Surgery, 2022)
The adoption of minimally invasive esophagectomy has been used for over a decade, and the chest part is evolving into a uniportal video-assisted thoracoscopic surgery (VATS) approach. Uniportal esophageal mobilization and anastomosis have many peculiar aspects, which include placement of the incision, alignment of instruments, and anastomosis. The incision is placed over the sixth intercostal space posterior axillary line. The esophagus is usually encircled at the level of the inferior pulmonary vein. The use of curved suction helps in the retraction of the esophagus and the exposure of the left main bronchus deep in the mediastinum. For intrathoracic anastomosis in Ivor Lewis esophagectomy, a completely side-to-side linear-stapled anastomosis is preferred. This anastomotic technique results in a long stapler line. The correct alignment of tissues and adequate anastomotic circumference are of utmost importance to prevent leaks or strictures. Perioperative and oncologic results in several series with uniportal VATS, esophageal mobilization, and anastomosis are comparable with open or other types of minimally invasive esophagectomy. Uniportal VATS for esophagectomy is feasible and fast with good results.